Creativity in teaching and learning in the Faculty Of Education of Malaysia public universities - Abu Bakar, Zainudin (2010)
Creativity and Innovation becomes important in the present day. It becomes main factor to the successfulness. Every parts of the society, including schools and higher institution, recognised the importance of the skills. In other words, students are expected to acquire the skills in order for them to compete in the challenging world at the later stage. As such, a study need to be conducted to explore the In regards to acquiring process, it becomes crucial to explore how creativity and innovation are being transmitted from one to the other. This study is therefore being conducted to investigate the implementation of creativity in teaching and learning among lecturers of Faculty of Education of the Malaysian public universities. All lecturers in the faculty of education are invited to involve in the study. Several aspects are investigated such as the knowledge, skills, and the implementation of creativity and innovation elements in the teaching and learning process. Online survey is used to collect the data and it has been emailed to them by their email address. Almost 200 lecturers have responded. Descriptive analysis is used to answer the research questions. The finding shows that the lecturer’s knowledge on creativity and innovation are in moderate level. Although they claimed that they have applied creativity in their teaching, findings showed that they are not really aware of their teaching, in regards to purposely make used of the creativity elements in their teaching. Several suggestions and recommendation are also provided.